University students’ knowledge and readiness to practice genomic nursing in Nigeria - Prisca O. Adejumo (Elsevier, 2021)
Introduction: Genetic nursing education provides knowledge of traits and inherited diseases. This has not been well integrated into nursing practice in Nigeria. Aim: This study evaluated university nursing students’ knowledge of genomic concepts and readiness to practice genomic nursing in Nigeria. Methods: A cross-sectional study was conducted. Three universities were purposively selected in Nigeria. A total of 136 participants were recruited using convenient sampling technique. A modified Genetic Nursing Concept Inventory questionnaire was distributed to participants in their classrooms. Data were analyzed with SPSS (23); descriptive data were presented in tables and figures with their mean and standard deviations. Chi-square test and multivariate analysis were used to ascertain association between variables at p < 0.05 level of significance. Results: Findings indicated that participants have poor knowledge (89%) and lack readiness (66%) to practice genomic nursing in Nigeria. Their knowledge influenced their readiness (χ2 = 21.033, df = 1, p = 0.001). Institution type was the most consistent predictor of knowledge (χ2 = 48.586, df = 2, p = 0.001) and readiness (OR = 14.817, p = 0.326, C.I. = 3.190, 319.57) as those in federal institution were more knowledgeable and prepared to practice genetic nursing. Participants perceived that poor funding, lack of trained personnel, and social/environmental factors could affect their readiness to practice genetic nursing. Conclusion: The study has brought to the fore that nursing students have low knowledge and were not ready to practice genetic nursing, efforts should be made to look into the adequacy of nursing training on genetic nursing and strategies needed for its integration in education and practice.